A novel phosphate-ceramic coating for high temperature oxidation resistance of Ti65 alloys. Issue 18 (15th December 2019) - Han, Rifei; Tariq, Naeem ul Haq; Li, Jiayi; Kong, Lingyan; Liu, Jianrong; Shan, Xiurong; Cui, Xinyu; Xiong, Tianying
Abstract: A novel phosphate-ceramic coating was developed for high-temperature oxidation protection of Ti65 titanium alloy. Aluminum phosphate binder was strategically mixed with Al2 O3 +SiC ceramic particles as the filler material and subsequently deposited on Ti65 titanium alloy by air spraying. High temperature oxidation behavior of the Ti65 substrate was studied in coated and un-coated state by performing series of isothermal oxidation and thermal shock tests at 650 °C. Microstructural and thermal evolutions under different conditions were investigated using scanning electron microscopy (SEM), electron-probe microanalysis (EPMA) and X-ray diffraction (XRD). It was revealed that under uncoated condition, the Ti65 alloy experienced severe oxidation and developed non-protective TiO2 oxide film. In contrast, phosphate-ceramic coated Ti65 alloy exhibited excellent oxidation resistance with small weight gain (0.35 mg/cm 2 ) compared with that of the uncoated Ti65 alloy (1.05 mg/cm 2 ). Microscopy results confirmed absence of TiO2 oxide scales at the coating-substrate interface. The significant enhancement in the oxidation resistance of the Ti65 alloy was attributed to the dense nature of the phosphate-ceramic protective coating with great thermal and chemical stability. Furthermore, the coating exhibited excellent thermal shock resistance for having compatible thermal expansion coefficient with the Ti65 alloy substrate.